Why we make mistakes : how we look without seeing, forget things in seconds, and are all pretty sure we are way above average - Hallinan, Joseph T. (Broadway Books, 2009)
Hallinan sets out to explore the captivating science of human error, and delves into psychology, neuroscience, and economics to discover why some of the same qualities that make us efficient also make us error-prone.